Dataset from Annual Acoustic Presence of Fin Whale (Balaenoptera physalus) Offshore Eastern Sicily, Central Mediterranean Sea - Sciacca Virginia; Caruso Francesco; Beranzoli Laura; Chierici Francesco; De Domenico Emilio; Embriaco Davide; Favali Paolo; Giovanetti Gabriele; Larosa Giuseppina; Marinaro Giuditta; Papale Elena; Pavan Gianni; et al. (Zenodo, 2015)
This dataset is form the study: Sciacca V., Caruso F.,Beranzoli L., Chierici F., De Domenico E., Embriaco D., Favali P., Giovanetti G., Larosa G., Marinaro G., Papale E., Pavan G., Pellegrino C., Pulvirenti S., Simeone F., Viola S., and G. Riccobene. "Annual Acoustic Presence of Fin Whale ( Balaenoptera physalus ) Offshore Eastern Sicily, Central Mediterranean Sea."PLoS ONE 10(11): e0141838. doi:10.1371/journal.pone.0141838 The archives labeled YYYYMM_Spectrograms.zip contain the data from each month of passive acousticrecording -MM-of the years -YYYY- 2012 and 2013. Data consistof the spectrograms (1-50 Hz) of 10-min audio recordings, in PNG format files. These data were used in the cited studyto verify the presence of fin whale calls. The archive labeled "NoiseData.zip" consists of two matrix (ASCII format)containing the recorded values of acoustic noise within the fin whale call frequency band.